Deuterium Tracer for Accurate Online Lube-Oil-Consumption Measurement: Stability, Compatibility and Tribological Characteristics - Martin Vareka; Bernhard Rossegger; Franz Novotny-Farkas; Michael Engelmayer; Andreas Wimmer (Lubricants, 2022)
Because of the impact of lubrication on the efficiency and the lifecycle cost and emissions, the lubricating-oil consumption (LOC) is one of the key indicators in the research and development of internal combustion engines. State-of-the-art methods for LOC measurement are based on the use of a certain tracer to track the oil consumption. However, all of the currently available tracers have their downsides (e.g., the use of a radioactive tracer, corrosive emissions, etc.). Therefore, in the course of this research project, a new tracer substance that is based on a stable nonradioactive isotope of hydrogen—deuterium—was developed and tested thoroughly. The LOC is monitored by a hydrogen/deuterium isotopic ration in the exhaust gas by using an isotopic water analyzer. Tribologically important properties, such as the viscosity, stability, and compatibility of the tracer were investigated by laboratory experiments by using several tools, such as infrared spectroscopy, gas chromatography, thermogravimetry, etc. The properties relevant to the applicability of the method, such as the accuracy and the reproducibility, were investigated by engine test-bench experiments. Finally, long-term stability tests of the tracer were conducted with a field test.